Dynamic water/fat separation and B0 inhomogeneity mapping—joint estimation using undersampled triple‐echo multi‐spoke radial FLASH. Issue 3 (29th April 2019) - Tan, Zhengguo; Voit, Dirk; Kollmeier, Jost M.; Uecker, Martin; Frahm, Jens
Abstract : Purpose: To achieve dynamic water/fat separation and B 0 field inhomogeneity mapping via model‐based reconstructions of undersampled triple‐echo multi‐spoke radial FLASH acquisitions. Methods: This work introduces an undersampled triple‐echo multi‐spoke radial FLASH sequence, which uses (i) complementary radial spokes per echo train for faster spatial encoding, (ii) asymmetric echoes for flexible and nonuniform echo spacing, and (iii) a golden angle increment across frames for optimal k‐space coverage. Joint estimation of water, fat, B 0 inhomogeneity, and coil sensitivity maps from undersampled triple‐echo data poses a nonlinear and non‐convex inverse problem which is solved by a model‐based reconstruction with suitable regularization. The developed methods are validated using phantom experiments with different degrees of undersampling. Real‐time MRI studies of the knee, liver, and heart are conducted without prospective gating or retrospective data sorting at temporal resolutions of 70, 158, and 40 ms, respectively. Results: Up to 18‐fold undersampling is achieved in this work. Even in the presence of rapid physiological motion, large B 0 field inhomogeneities, and phase wrapping, the model‐based reconstruction yields reliably separated water/fat maps in conjunction with spatially smooth inhomogeneity maps. Conclusions: The combination of a triple‐echo acquisition and joint reconstruction technique provides a practical solution to time‐resolved and motion robust water/fat separation at high spatial and temporal resolution.